Adhesive tape
By using foam substrate and bio-derived carbon in the adhesive tape, and combining block copolymers with (meth)acrylic monomers, the existing adhesive tape is solved, and the problem of difficulty in taking into account the adhesive strength, impact resistance and softness is achieved, and an efficient and environmentally friendly adhesive tape is achieved.
Patent Information
- Application Number
- CN202180049643.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-28
- Filing Date
- 2021-10-27
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-10-27
AI Technical Summary
Existing adhesive tapes are difficult to take into account high adhesion, impact resistance and softness, and their environmental burden is high.
Using an adhesive tape having a foamed substrate and at least one adhesive layer, the foamed substrate contains a block copolymer from blocks of (meth)acrylic monomers and contains bio-derived carbon.
The excellent softness and impact resistance of the adhesive tape are achieved while reducing environmental burden.
Smart Images

Figure BDA0004048606640000031 
Figure BDA0004048606640000041 
Figure BDA0004048606640000161
Abstract
Description
Technical Field
[0001] The present invention relates to adhesive tapes. Background Art
[0002] Adhesive tapes are used to assemble mobile electronic devices such as mobile phones and PDAs (for example, Patent Documents 1 and 2). In addition, adhesive tapes are also used to fix vehicle-mounted electronic device components such as vehicle-mounted panels to the vehicle itself.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2009-242541
[0006] Patent Document 2: Japanese Patent Application Publication No. 2009-258274 Summary of the invention
[0007] Problems to be solved by the invention
[0008] Adhesive tapes used for fixing mobile electronic equipment components, vehicle-mounted electronic equipment components, etc. require high adhesive force and impact resistance that does not peel off even when impacted. On the other hand, in recent years, the shapes of mobile electronic equipment, vehicle-mounted electronic equipment, etc. tend to be more complicated with the high functionality, and there are cases where adhesive tapes are attached to height differences, corners, non-planar parts, etc. for use. In such a case, the adhesive tape is required to have excellent flexibility that can follow the shape of the adherend. However, the previous adhesive tapes cannot fully take into account both impact resistance and flexibility, and a higher level of adhesive tape that can take into account both impact resistance and flexibility is required. In addition, due to the recent rise in environmental awareness, the functionality of the adhesive tape is not to mention, and products with lower environmental burden are also required.
[0009] An object of the present invention is to provide a pressure-sensitive adhesive tape which has excellent flexibility and impact resistance and has a low environmental load.
[0010] Means for solving problems
[0011] The present invention is a pressure-sensitive adhesive tape comprising a foam substrate and at least one pressure-sensitive adhesive layer, wherein the foam substrate comprises a block copolymer having a block derived from a (meth)acrylic monomer, and the pressure-sensitive adhesive tape comprises biogenic carbon.
[0012] The present invention is described in detail below.
[0013] The pressure-sensitive adhesive tape of the present invention comprises a foam substrate and at least one pressure-sensitive adhesive layer.
[0014] By using a foam substrate as the substrate of the adhesive tape, the adhesive tape of the present invention can exhibit excellent flexibility and impact resistance. The foam substrate may have a continuous cell structure or a closed cell structure, preferably a closed cell structure. The foam substrate may be a single-layer structure or a multi-layer structure.
[0015] The adhesive tape of the present invention contains biogenic carbon.
[0016] By using a bio-derived material for an adhesive tape, an adhesive tape with low environmental burden can be obtained. The bio-derived carbon may be contained in the foam substrate or in the adhesive layer. When the adhesive tape of the present invention has a layer other than the foam substrate and the adhesive layer, it may be contained in the layer. From the perspective of achieving excellent flexibility and impact resistance, it is preferred that the foam substrate contains bio-derived carbon.
[0017] The foam substrate contains a block copolymer having a block derived from a (meth)acrylic monomer.
[0018] By making the foam substrate contain a block copolymer having a block from a (meth) acrylic monomer, excellent flexibility and impact resistance can be exerted. In addition, by having a block from a (meth) acrylic monomer, the obtained adhesive tape can be given heat resistance, and deformation and peeling of the adhesive tape can be suppressed even if it is exposed to a high temperature environment for a long time.
[0019] The block copolymer having a block derived from a (meth)acrylic monomer is not particularly limited as long as it has a block derived from a (meth)acrylic monomer. Among them, from the perspective of further improving flexibility and impact resistance, a block copolymer having a block derived from a monomer having a rigid structure (hereinafter also referred to as a hard block) and a block derived from a (meth)acrylic monomer is preferred.
[0020] The block copolymer having a hard block and a block from a (meth) acrylic monomer, the two blocks are difficult to be compatible, and sometimes constitutes: in the sea of blocks from (meth) acrylic monomers, the islands formed by the aggregation of hard blocks are scattered with uneven phase separation structures. It is also believed that the above-mentioned islands become suspected crosslinking points, giving the copolymer rubber elasticity, and can give the obtained adhesive tape high softness and impact resistance. It is also believed that if a crosslinking functional group is introduced into the hard block, the obtained adhesive tape can be given further softness and impact resistance. The above-mentioned block copolymer having a hard block and a block from a (meth) acrylic monomer can be any structure such as a diblock structure and a triblock structure. From the perspective of further improving softness and impact resistance, it is preferably equipped with a triblock structure having a block from a (meth) acrylic monomer between the hard blocks. In addition, the above-mentioned block copolymer having a hard block and a block from a (meth) acrylic monomer can also be a graft copolymer. The graft copolymer may have a hard block in the side chain and a block derived from a (meth)acrylic monomer in the main chain. Examples of the graft copolymer include styrene macromonomer-(meth)acrylic monomer copolymers.
[0021] As for the above-mentioned hard block, there is no particular limitation as long as it has a structure derived from a monomer having a rigid structure. It can be a single polymer of a monomer having a rigid structure, or a copolymer containing multiple monomers, wherein the multiple monomers contain a monomer having a rigid structure. As the above-mentioned monomer having a rigid structure, for example, vinyl aromatic compounds, compounds having a cyclic structure, compounds with short side chain substituents (for example, the number of carbon atoms in the main chain of the side chain substituent is 2 or less), etc. can be listed. In addition, the above-mentioned hard block can have a structure derived from methyl methacrylate. Among them, from the perspective of better improving impact resistance, the above-mentioned hard block more preferably has a structure derived from a vinyl aromatic compound monomer. As the above-mentioned vinyl aromatic compound monomer, for example, styrene, α-methylstyrene, p-methylstyrene, chlorostyrene, etc. can be listed. Among them, from the perspective of further improving impact resistance, styrene is preferred. It should be noted that in this specification, the structure derived from the vinyl aromatic compound monomer refers to the structure shown in the following general formula (1) and (2).
[0022] [Chemical formula 1]
[0023]
[0024] In formula (1) and (2), R 1 represents a substituent having an aromatic ring. 1 , phenyl, methylphenyl, chlorophenyl, etc. can be listed.
[0025] When the block copolymer has the structure derived from the vinyl aromatic compound monomer, the content of the structure derived from the vinyl aromatic compound monomer in the block copolymer is preferably 1% by weight or more and 30% by weight or less.
[0026] By setting the content of the structure derived from the vinyl aromatic compound monomer within the above range, the flexibility and impact resistance can be further improved. The more preferred lower limit of the content of the structure derived from the vinyl aromatic compound monomer is 1.5% by weight, the further preferred lower limit is 2% by weight, the particularly preferred lower limit is 2.5% by weight, the more preferred upper limit is 24% by weight, the further preferred upper limit is 19% by weight, the particularly preferred upper limit is 16% by weight, and the particularly preferred upper limit is 8% by weight.
[0027] The hard block preferably has a structure derived from a monomer having a crosslinkable functional group.
[0028] If the hard block has a crosslinkable functional group, the rubber elasticity of the block copolymer is improved by crosslinking, and the softness and impact resistance can be further improved. The above-mentioned crosslinkable functional group may be crosslinked or not crosslinked, even if it is a structure that is not crosslinked, the cohesion in the block is improved by the interaction between the functional groups, and the softness and impact resistance are improved, but it is more preferably crosslinked. It should be noted that in this specification, the structure from the monomer having a crosslinkable functional group refers to the structure shown in the following general formula (3) and (4).
[0029] [Chemical formula 2]
[0030]
[0031] Here, R 2 represents a substituent containing at least one functional group. Examples of the functional group include carboxyl, hydroxyl, epoxy, double bond, triple bond, amino, amide, nitrile, etc. It should be noted that the substituent R 2 An alkyl group, an ether group, a carbonyl group, an ester group, a carbonate group, an amide group, a carbamate group or the like may be contained as its constituent elements.
[0032] The above-mentioned monomer with crosslinking functional group is not particularly limited, for example, monomers containing carboxyl groups, monomers containing hydroxyl groups, monomers containing epoxy groups, monomers containing double bonds, monomers containing triple bonds, monomers containing amino groups, monomers containing amide groups, monomers containing nitrile groups, etc. can be listed. Among them, from the perspective of further improving flexibility and impact resistance, it is preferred to select at least one from monomers containing hydroxyl groups, monomers containing carboxyl groups, monomers containing epoxy groups, monomers containing amide groups, monomers containing double bonds and monomers containing triple bonds. As monomers containing hydroxyl groups, 4-hydroxybutyl (methyl) acrylate, 2-hydroxyethyl (methyl) acrylate, etc. can be listed. As the above-mentioned monomers containing carboxyl groups, (methyl) acrylic acid, etc. can be listed. As monomers containing epoxy groups, glycidyl (methyl) acrylate, etc. can be listed. As monomers containing amide groups, (methyl) acrylamide, etc. can be listed. As monomers containing double bonds, allyl (methyl) acrylate, hexanediol di(methyl) acrylate, etc. can be listed. As monomers containing triple bonds, propargyl (methyl) acrylate, etc. can be listed. Among them, from the viewpoint of providing the pressure-sensitive adhesive tape with more excellent flexibility and impact resistance, a carboxyl group-containing monomer is preferred, a (meth)acrylic acid monomer is more preferred, and acrylic acid is further preferred.
[0033] When the hard block is a copolymer of the monomer having a rigid structure and the monomer having a crosslinkable functional group, the hard block preferably contains 0.1 wt % or more and 30 wt % or less of the structure derived from the monomer having a crosslinkable functional group.
[0034] By setting the content of the structure derived from the monomer having a crosslinkable functional group in the hard block to be within the above range, the flexibility and impact resistance can be further improved. The more preferred lower limit of the content of the structure derived from the monomer having a crosslinkable functional group is 0.5% by weight, and the further preferred lower limit is 1% by weight, and the more preferred upper limit is 25% by weight, and the further preferred upper limit is 20% by weight.
[0035] The (meth) acrylic acid monomers that are the raw materials of the blocks from the (meth) acrylic acid monomers are not particularly limited as long as they have the flexibility to show rubber elasticity. For example, methyl (meth) acrylate, ethyl (meth) acrylate, propyl (meth) acrylate, butyl (meth) acrylate, pentyl (meth) acrylate, hexyl (meth) acrylate, heptyl (meth) acrylate, octyl (meth) acrylate, 2-ethylhexyl (meth) acrylate, nonyl (meth) acrylate, decyl (meth) acrylate, dodecyl (meth) acrylate, lauryl (meth) acrylate, isostearyl (meth) acrylate, etc. can be cited. Among them, from the perspective of easily taking into account heat resistance and flexibility, methyl acrylate, ethyl acrylate, butyl (meth) acrylate, 2-ethylhexyl (meth) acrylate are preferred, and methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate are more preferred. It should be noted that the above-mentioned (meth) acrylic acid monomers can be used alone or in combination.
[0036] The (meth)acrylic acid-based monomer preferably contains a (meth)acrylic acid-based monomer containing biogenic carbon.
[0037] By using a (meth)acrylic monomer containing biogenic carbon, a pressure-sensitive adhesive tape with a lower environmental burden can be obtained.
[0038] While carbon from biological sources contains a certain percentage of radioactive isotopes (C-14), carbon from petroleum sources contains almost no C-14. Therefore, the content of carbon from biological sources can be calculated by measuring the concentration of C-14 contained in the object. Specifically, it can be measured according to the standard ASTM D6866 that is widely used in the bioplastics industry.
[0039] Examples of the (meth)acrylic acid monomer containing biogenic carbon, i.e., a (meth)acrylic acid monomer that can be produced from a biogenic raw material, include butyl (meth)acrylate, n-heptyl (meth)acrylate, 1-methylheptyl (meth)acrylate, n-octyl (meth)acrylate, lauryl (meth)acrylate, n-stearyl (meth)acrylate, isostearyl (meth)acrylate, behenyl (meth)acrylate, isobornyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, etc. Among them, the (meth)acrylic acid monomer containing biogenic carbon is preferably a (meth)acrylic acid monomer having an alkyl group with 7 to 12 carbon atoms, from the viewpoint of further improving heat resistance and impact resistance. It is believed that by using such a monomer, the molecular weight between the entanglement points of the polymer becomes relatively large, and the polymer is easily elongated when the adhesive tape is impacted, which can alleviate the impact. Examples of the (meth) acrylic monomer having an alkyl group with 7 to 12 carbon atoms include n-heptyl acrylate, 1-methylheptyl acrylate, n-octyl acrylate, lauryl acrylate, lauryl methacrylate, isobornyl acrylate, etc. Among them, n-heptyl acrylate or n-octyl acrylate is preferred from the perspective of being able to produce an adhesive tape with better heat resistance and impact resistance. The (meth) acrylic monomer containing biogenic carbon may be used alone or in combination of two or more.
[0040] The (meth)acrylic acid-based monomer containing biogenic carbon is preferably a (meth)acrylic acid-based monomer having a homopolymer having a glass transition temperature Tg of -40°C or lower.
[0041] By making the Tg of the (meth)acrylic monomer containing biogenic carbon into a homopolymer within the above range, the impact resistance can be further improved. The above glass transition temperature can be obtained as follows: for the substance obtained by making the (meth)acrylic monomer containing biogenic carbon into a homopolymer with a weight average molecular weight of 100,000 to 1,000,000, a differential scanning calorimeter (for example, 220C manufactured by SEIKO INSTRUMENTS, etc.) is used to measure it in the atmosphere at a heating rate of 10°C / minute. It should be noted that the above glass transition temperature can be adjusted according to the type of (meth)acrylic monomer. As the (meth)acrylic monomer containing biogenic carbon that satisfies the above Tg, n-heptyl acrylate, n-octyl acrylate, lauryl methacrylate, etc. can be listed.
[0042] The block derived from the (meth)acrylic acid-based monomer may be made of a monomer other than the (meth)acrylic acid-based monomer within a range not impairing the effects of the present invention.
[0043] The block copolymer preferably contains more than 1% by weight and less than 40% by weight of the hard block. By making the content of the hard block within the above range, a foam substrate having excellent flexibility, impact resistance and heat resistance can be formed. From the viewpoint of further improving flexibility, impact resistance and heat resistance, the more preferred lower limit of the content of the hard block is 2% by weight, the more preferred lower limit is 2.5% by weight, the particularly preferred lower limit is 3% by weight, the more preferred upper limit is 35% by weight, the further preferred upper limit is 30% by weight, the further preferred upper limit is 26% by weight, the further preferred upper limit is 20% by weight, the particularly preferred upper limit is 17% by weight, and the particularly preferred upper limit is 8% by weight.
[0044] The block copolymer preferably has a polymerization average molecular weight of 50,000 to 800,000.
[0045] By making the weight average molecular weight of the block copolymer within the above range, flexibility, impact resistance and heat resistance can be further improved. The more preferred lower limit of the polymerization average molecular weight of the above block copolymer is 75000, and the more preferred upper limit is 600000. It should be noted that the above weight average molecular weight can be measured, for example, by GPC method, and Waters "2690Separations Module" can be used as a measuring instrument, Showa Denko "GPC KF-806L" is used as a chromatographic column, ethyl acetate is used as a solvent, and the sample flow rate is 1mL / min, and the chromatographic column temperature is 40°C.
[0046] As a method for obtaining the above-mentioned block copolymer, there can be cited a method of allowing the raw material monomers of the hard block and the block derived from the (meth)acrylic monomer to undergo free radical reaction in the presence of a polymerization initiator, respectively, to obtain the hard block and the block derived from the (meth)acrylic monomer, and then reacting the two. In addition, there can also be cited a method of obtaining the hard block by the above method, and then continuously adding the raw material monomers of the block derived from the (meth)acrylic monomer to copolymerize. As a method for carrying out the above-mentioned free radical reaction, i.e., a polymerization method, a conventionally known method can be used, for example, solution polymerization (boiling point polymerization or constant temperature polymerization), emulsion polymerization, suspension polymerization, bulk polymerization, etc. can be cited.
[0047] The foam substrate may contain additives such as an antistatic agent, a release agent, an antioxidant, a weathering agent, a crystal nucleating agent, and resin modifiers such as polyolefin, polyester, polyamide, and elastomer.
[0048] The apparent density of the foam substrate is preferably 0.3 g / cm 3 Above 0.95g / cm 3 the following.
[0049] By setting the apparent density of the foam substrate alone within the above range, a pressure-sensitive adhesive tape having better flexibility and impact resistance can be obtained while maintaining strength. From the viewpoint of further improving the strength, flexibility and impact resistance of the pressure-sensitive adhesive tape, a more preferred lower limit of the apparent density of the foam substrate is 0.33 g / cm 3 The more preferred upper limit is 0.9 g / cm 3 The lower limit is preferably 0.35 g / cm 3 The upper limit is preferably 0.88 g / cm 3 .
[0050] In addition, the said apparent density can be measured using the electronic density meter (for example, the product of MIRAGE CORPORATION, "ED120T") based on JIS K 7222.
[0051] The foam substrate preferably has a gel fraction of 90% or less.
[0052] By making the gel fraction of the foam substrate within the above range, the impact resistance of the obtained adhesive tape can be further improved. From the viewpoint of further improving the impact resistance of the adhesive tape, the more preferred upper limit of the gel fraction is 85%, and the further preferred upper limit is 80%. The lower limit of the gel fraction is not particularly limited, for example, it is 10% or more, especially 20% or more, and especially 35% or more. The gel fraction can be adjusted by cross-linking at least one of the hard block and the block from the (meth) acrylic monomer. It should be noted that the gel fraction can be measured by the following method.
[0053] Only 0.1 g of the foam substrate was taken out from the obtained adhesive tape, immersed in 50 ml of ethyl acetate, and shaken for 24 hours with a shaker at a temperature of 23 degrees and 120 rpm. After shaking, the ethyl acetate and the foam substrate swollen by absorbing ethyl acetate were separated using a metal mesh (mesh #200 mesh). The separated foam substrate was dried at 110°C for 1 hour. The weight of the foam substrate including the dried metal mesh was measured, and the gel fraction of the foam substrate was calculated using the following formula.
[0054] Gel fraction (weight %) = 100 × (W1-W2) / W0
[0055] (W0: initial weight of foam substrate, W1: weight of foam substrate including metal mesh after drying, W2: initial weight of metal mesh)
[0056] Regarding the foam substrate, it is preferred to form a cross-linked structure between the main chains of the resin constituting the foam substrate by adding a cross-linking agent. By forming a cross-linked structure between the main chains of the resin constituting the foam substrate, the peeling stress applied intermittently can be dispersed, and the heat resistance and impact resistance of the adhesive tape can be further improved. The cross-linking agent is not particularly limited and can be appropriately selected according to the functional group possessed by the resin constituting the foam substrate. Specifically, for example, isocyanate cross-linking agents, aziridine cross-linking agents, epoxy cross-linking agents, metal chelate cross-linking agents, etc. can be cited. Among them, from the perspective of being able to cross-link the resin with alcoholic hydroxyl and carboxyl groups that can better improve flexibility and impact resistance, epoxy cross-linking agents or isocyanate cross-linking agents are preferably used. It should be noted that the isocyanate cross-linking agent cross-links the alcoholic hydroxyl and carboxyl groups in the resin constituting the foam substrate with the isocyanate groups of the cross-linking agent. In addition, the epoxy cross-linking agent cross-links the carboxyl groups in the resin constituting the foam substrate with the epoxy groups of the cross-linking agent.
[0057] The amount of the crosslinking agent added is preferably 0.01 parts by weight or more and 10 parts by weight or less, and more preferably 0.1 parts by weight or more and 7 parts by weight or less, based on 100 parts by weight of the resin that is the main component of the foam substrate.
[0058] The average cell diameter of cells in the foam substrate is preferably 80 μm or less.
[0059] When the average cell diameter of the foam substrate is within the above range, the balance among the strength, flexibility, and impact resistance of the obtained pressure-sensitive adhesive tape can be further improved.
[0060] The average cell diameter of the foam substrate is more preferably 60 μm or less, and further preferably 55 μm or less. The lower limit of the average cell diameter of the foam substrate is not particularly limited, but is preferably 20 μm or more, and more preferably 30 μm or more, from the viewpoint of ensuring the flexibility of the belt.
[0061] In addition, the said average cell diameter can be measured by the following method.
[0062] First, the foam substrate is cut into 50 mm squares, immersed in liquid nitrogen for 1 minute, and then cut with a razor at a plane perpendicular to the thickness direction of the foam substrate. Next, an electron microscope (e.g., "VHX-900" manufactured by KEYENCE) is used to take a magnified photograph of the cut surface at a magnification of 200 times, and the longest cell diameter (diameter of the bubble) is measured for all cells existing within the range of thickness × 2 mm. This operation is repeated 5 times, and the average cell diameter is calculated by averaging all the obtained cell diameters.
[0063] The thickness of the foam substrate is not particularly limited, but the preferred lower limit is 40 μm and the preferred upper limit is 2900 μm. By making the thickness of the foam substrate within the above range, the adhesive tape of the present invention can be suitably used for fixing mobile electronic device components, vehicle-mounted electronic device components, etc. From the viewpoint of being more suitable for fixing the above components, etc., the more preferred lower limit of the thickness of the foam substrate is 60 μm, the more preferred upper limit is 1900 μm, the further preferred lower limit is 80 μm, the further preferred upper limit is 1400 μm, the particularly preferred lower limit is 100 μm, and the particularly preferred upper limit is 1000 μm.
[0064] As long as the foam substrate has a bubble structure, the manufacturing method is not particularly limited. As a manufacturing method, for example, there can be cited: a method in which the foam substrate is manufactured by the action of a foaming gas; a method in which the foam substrate is manufactured by combining hollow spheres in a raw material matrix. Among them, the foam manufactured by the latter method is called a composite foam plastic, and from the perspective of better impact resistance and heat resistance, the foam substrate is preferably a composite foam plastic. By setting the foam substrate as a composite foam plastic, a foam of a closed bubble type with a uniform size distribution of foamed bubbles is obtained, so the overall density of the foam substrate becomes more stable, and the impact resistance can be further improved. In addition, compared with other foams, irreversible rupture under high temperature and high pressure is difficult to occur in composite foam plastics, so it shows higher heat resistance. As composite foam plastics, there are: composite foam plastics having a foaming structure containing hollow inorganic particles; and composite foam plastics having a foaming structure containing hollow organic particles. From the perspective of softness, composite foam plastics having a foaming structure containing hollow organic particles are preferred.
[0065] Examples of the hollow organic particles include Expancel DU series (manufactured by Nippon Fillite Co., Ltd.) and ADVANCELL EM series (manufactured by Sekisui Chemical Co., Ltd.). Among them, Expancel 461-20 (average cell diameter after foaming under optimal conditions: 20 μm), Expancel 461-40 (average cell diameter after foaming under optimal conditions: 40 μm), Expancel 043-80 (average cell diameter after foaming under optimal conditions: 80 μm), and ADVANCELL EML101 (average cell diameter after foaming under optimal conditions: 50 μm) are preferred from the viewpoint of facilitating the design of the cell diameter after foaming to a higher effect.
[0066] When the foam substrate includes a foam other than the syntactic foam, the foaming agent is not particularly limited, and a conventionally known foaming agent such as a thermal decomposition type foaming agent can be used.
[0067] The adhesive layer is not particularly limited, and examples thereof include acrylic adhesive layers, rubber adhesive layers, urethane adhesive layers, silicone adhesive layers, etc. Among them, acrylic adhesive layers containing acrylic copolymers are preferred because they are excellent in heat resistance and can be bonded to a wide variety of substrates.
[0068] The acrylic copolymer constituting the acrylic adhesive layer is preferably obtained by copolymerizing a monomer mixture containing butyl acrylate and / or 2-hexylethyl acrylate, from the viewpoint of improving the initial viscosity and making the ease of attachment at low temperatures better. Among them, it is more preferably obtained by copolymerizing a monomer mixture containing butyl acrylate and 2-hexylethyl acrylate. That is, it is preferably a copolymer having a structural unit derived from butyl acrylate and / or a structural unit derived from 2-ethylhexyl acrylate, and more preferably a copolymer having a structural unit derived from butyl acrylate and a structural unit derived from 2-ethylhexyl acrylate.
[0069] In addition, the acrylic copolymer is preferably obtained by copolymerizing a (meth)acrylic monomer mixture containing biogenic carbon from the viewpoint of being able to produce an adhesive tape with a lower environmental burden. As the (meth)acrylic monomer containing biogenic carbon, butyl acrylate, n-heptyl acrylate, 1-methylheptyl acrylate, n-octyl acrylate, and lauryl methacrylate are particularly preferred.
[0070] The preferred lower limit of the content of the butyl acrylate in the total monomer mixture is 40% by weight, and the preferred upper limit is 80% by weight. That is, the preferred lower limit of the content of the structural unit derived from butyl acrylate in the acrylic copolymer is 40% by weight, and the preferred upper limit is 80% by weight. By making the content of the butyl acrylate within the above range, high adhesive force and viscosity can be achieved.
[0071] The preferred lower limit of the content of the above-mentioned 2-ethylhexyl acrylate in the entire monomer mixture is 10% by weight, the preferred upper limit is 100% by weight, the more preferred lower limit is 30% by weight, the more preferred upper limit is 80% by weight, the further preferred lower limit is 50% by weight, and the further preferred upper limit is 60% by weight.
[0072] That is, the content of the structural unit derived from 2-ethylhexyl acrylate in the acrylic copolymer preferably has a lower limit of 10% by weight, an upper limit of 100% by weight, a more preferred lower limit of 30% by weight, a more preferred upper limit of 80% by weight, a further preferred lower limit of 50% by weight, and a further preferred upper limit of 60% by weight. When the content of 2-ethylhexyl acrylate is within the above range, high adhesive force can be exerted.
[0073] The preferred lower limit of the content of the above-mentioned n-heptyl acrylate containing biogenic carbon in the total monomer mixture is 25% by weight, and the preferred upper limit is 100% by weight. That is, in the above-mentioned acrylic copolymer, the preferred lower limit of the content of the structural unit derived from the above-mentioned n-heptyl acrylate containing biogenic carbon is 25% by weight, and the preferred upper limit is 100% by weight.
[0074] The lower limit of the content of the structural unit derived from n-heptyl acrylate is more preferably 48% by weight, further preferably 50% by weight, further more preferably 60% by weight, still more preferably 70% by weight, and still more preferably 80% by weight. The upper limit of the content of the structural unit derived from n-heptyl acrylate is not particularly limited, and may be 100% by weight. From the perspective of preferably allowing the acrylic copolymer to further have a structural unit derived from a monomer having a crosslinkable functional group, the upper limit is preferably 99% by weight, and the more preferably upper limit is 97% by weight.
[0075] The preferred lower limit of the content of the (meth)acrylic acid monomer containing biogenic carbon in the total monomer mixture is 50% by weight, the preferred upper limit is 100% by weight, the more preferred lower limit is 80% by weight, and the more preferred upper limit is 98% by weight. That is, in the acrylic acid copolymer, the preferred lower limit of the content of the structural unit derived from the (meth)acrylic acid monomer containing biogenic carbon is 50% by weight, the preferred upper limit is 100% by weight, the more preferred lower limit is 80% by weight, and the more preferred upper limit is 98% by weight.
[0076] When the content of the (meth)acrylic acid-based monomer containing biogenic carbon is within the above range, both high adhesive strength and reduced environmental burden can be achieved.
[0077] The monomer mixture may contain other copolymerizable monomers other than butyl acrylate and 2-ethylhexyl acrylate as required. Examples of the other copolymerizable monomers include (meth)acrylic acid alkyl esters having an alkyl group with 1 to 18 carbon atoms and functional monomers.
[0078] Examples of the alkyl (meth)acrylates having an alkyl group with 1 to 18 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, tridecyl methacrylate, and stearyl (meth)acrylate. Examples of the functional monomers include hydroxyalkyl (meth)acrylates, glycerol dimethacrylate, glycidyl (meth)acrylate, 2-methacryloyloxyethyl isocyanate, (meth)acrylic acid, itaconic acid, maleic anhydride, crotonic acid, maleic acid, and fumaric acid.
[0079] To copolymerize the above monomer mixture to obtain the above acrylic copolymer, it is only necessary to subject the above monomer mixture to a radical reaction in the presence of a polymerization initiator. As a method for subjecting the above monomer mixture to a radical reaction, that is, a polymerization method, a conventionally well-known method can be used. For example, solution polymerization (boiling point polymerization or isothermal polymerization), emulsion polymerization, suspension polymerization, bulk polymerization, etc. can be cited.
[0080] The weight-average molecular weight (Mw) of the above acrylic copolymer preferably has a lower limit of 400,000 and a preferred upper limit of 1,500,000. By making the weight-average molecular weight of the above acrylic copolymer within the above range, high adhesiveness can be exhibited. From the viewpoint of further improving the adhesiveness, a more preferred lower limit of the above weight-average molecular weight is 500,000, and a more preferred upper limit is 1,400,000.
[0081] It should be noted that the weight-average molecular weight (Mw) is the weight-average molecular weight in terms of standard polystyrene based on GPC (Gel Permeation Chromatography).
[0082] The preferred upper limit of the ratio (Mw / Mn) of the weight-average molecular weight (Mw) to the number-average molecular weight (Mn) of the above acrylic copolymer is 10.0. If Mw / Mn is 10.0 or less, the proportion of low-molecular components is suppressed, and the above adhesive layer softens at high temperatures, and a decrease in bulk strength (Japanese: バルク強度) and a decrease in adhesive strength are suppressed. From the same viewpoint, a more preferred upper limit of Mw / Mn is 5.0, and a further preferred upper limit is 3.0.
[0083] The above adhesive layer may also contain a tackifying resin.
[0084] As the above tackifying resin, for example, rosin ester resins, hydrogenated rosin resins, terpene resins, terpene phenol resins, coumarone indene resins, alicyclic saturated hydrocarbon resins, C5 petroleum resins, C9 petroleum resins, C5-C9 copolymerized petroleum resins, etc. can be cited. These tackifying resins can be used alone or in combination of two or more.
[0085] The content of the above tackifying resin is not particularly limited, and relative to 100 parts by weight of the resin (for example, acrylic copolymer) that is the main component of the above adhesive layer, the preferred lower limit is 10 parts by weight, and the preferred upper limit is 60 parts by weight. If the content of the above tackifying resin is 10 parts by weight or more, a decrease in the adhesiveness of the above adhesive layer can be suppressed. If the content of the above tackifying resin is 60 parts by weight or less, a decrease in adhesiveness or tackiness due to hardening of the above adhesive layer can be suppressed.
[0086] About the above-mentioned adhesive layer, it is preferred to form a cross-linked structure between the main chains of the resin (for example, the above-mentioned acrylic copolymer, the above-mentioned tackifying resin, etc.) constituting the above-mentioned adhesive layer by adding a cross-linking agent. The above-mentioned cross-linking agent is not particularly limited, and for example, isocyanate cross-linking agents, aziridine cross-linking agents, epoxy cross-linking agents, metal chelate type cross-linking agents, etc. can be cited. Among them, isocyanate cross-linking agents are preferably used. By adding an isocyanate cross-linking agent to the above-mentioned adhesive layer, the isocyanate group of the isocyanate cross-linking agent reacts with the alcoholic hydroxyl group in the resin (for example, the above-mentioned acrylic copolymer, the above-mentioned tackifying resin, etc.) constituting the above-mentioned adhesive layer, and the above-mentioned adhesive layer is cross-linked. If a cross-linked structure is formed between the main chains of the resin constituting the above-mentioned adhesive layer, the above-mentioned adhesive layer can disperse the peeling stress applied intermittently, and the adhesive force of the adhesive tape is further improved.
[0087] The amount of the crosslinking agent added is preferably 0.01 to 10 parts by weight, more preferably 0.1 to 7 parts by weight, based on 100 parts by weight of the resin (for example, the acrylic copolymer) that is the main component of the pressure-sensitive adhesive layer.
[0088] The adhesive layer may contain a silane coupling agent for the purpose of improving adhesive strength. The silane coupling agent is not particularly limited, and examples thereof include epoxy silanes, acrylic silanes, methacrylic silanes, amino silanes, and isocyanate silanes.
[0089] The adhesive layer may contain a coloring material for the purpose of imparting light-shielding properties. The coloring material is not particularly limited, and examples thereof include carbon black, aniline black, titanium oxide, etc. Among them, carbon black is preferred because it is relatively cheap and has stable chemical properties.
[0090] The pressure-sensitive adhesive layer may contain conventionally known fine particles and additives such as inorganic fine particles, conductive fine particles, an antioxidant, a foaming agent, an organic filler, and an inorganic filler, as required.
[0091] The thickness of the adhesive layer is not particularly limited, but the preferred lower limit is 0.01 mm, and the preferred upper limit is 0.1 mm. By making the thickness of the adhesive layer within the above range, the adhesive tape of the present invention can be suitably used for fixing mobile electronic device components, vehicle-mounted electronic device components, etc. From the viewpoint of being suitable for fixing the above components, etc., the more preferred lower limit of the thickness of the adhesive layer is 0.015 mm, and the more preferred upper limit is 0.09 mm.
[0092] The pressure-sensitive adhesive tape of the present invention may include a resin layer on at least one surface of the foam substrate.
[0093] By having the resin layer, the strength of the obtained adhesive tape is improved, so the impact resistance can be further improved, and in particular, the durability (tumbling resistance) when subjected to repeated impacts can be improved. The resin layer can be formed on one side or both sides of the foam substrate, preferably on one side of the foam substrate.
[0094] The resin constituting the resin layer is preferably heat-resistant. Examples of the heat-resistant resin constituting the resin layer include polyester resins such as polyethylene terephthalate, acrylic resins, silicone resins, phenolic resins, polyimides, polycarbonates, and the like. Among them, acrylic resins and polyester resins are preferred, and polyethylene terephthalate is more preferred, from the perspective of obtaining an adhesive tape having excellent flexibility.
[0095] The resin layer may be colored. By coloring the resin layer, light-shielding properties can be imparted to the pressure-sensitive adhesive tape.
[0096] The method of coloring the resin layer is not particularly limited, and examples thereof include a method of kneading particles of carbon black, titanium oxide, or the like, or fine bubbles into the resin constituting the resin layer; a method of coating the surface of the resin layer with ink, and the like.
[0097] The resin layer may contain conventionally known fine particles and additives such as inorganic fine particles, conductive fine particles, a plasticizer, a thickener, an ultraviolet absorber, an antioxidant, a foaming agent, an organic filler, and an inorganic filler, as required.
[0098] The thickness of the resin layer is not particularly limited, but the preferred lower limit is 5 μm and the preferred upper limit is 100 μm. By making the thickness of the resin layer within the above range, the operability and impact resistance of the adhesive tape can be taken into account. From the viewpoint of further taking into account the operability and impact resistance, the more preferred lower limit of the thickness of the resin layer is 10 μm and the more preferred upper limit is 70 μm.
[0099] The pressure-sensitive adhesive tape of the present invention may include other layers other than the foam substrate and the pressure-sensitive adhesive layer as necessary.
[0100] The adhesive tape of the present invention preferably has a ratio of the thickness of the adhesive layer to the thickness of the foam substrate (adhesive layer thickness / foam substrate thickness) of 0.1 or more and 2 or less. By making the ratio of the thickness of the adhesive layer to the foam substrate within the above range, the strength of the adhesive tape as a whole obtained is improved, so the impact resistance can be further improved. The ratio of the thickness of the above-mentioned adhesive layer to the thickness of the foam substrate is more preferably 0.15 or more, more preferably 1.2 or less. It should be noted that the thickness of the above-mentioned adhesive layer refers to the total thickness of the adhesive layers on both sides.
[0101] The thickness of the adhesive tape of the present invention is not particularly limited, but the preferred lower limit is 0.04 mm, and the more preferred lower limit is 0.05 mm, and the preferred upper limit is 2 mm, and the more preferred upper limit is 1.5 mm. By making the thickness of the adhesive tape of the present invention within the above range, an adhesive tape with excellent handleability can be obtained.
[0102] The pressure-sensitive adhesive tape of the present invention preferably contains 10% by weight or more of biogenic carbon. A biogenic carbon content of 10% by weight or more is a criterion for a "bio-based product."
[0103] By making the content of biogenic carbon in the adhesive tape of the present invention 10% by weight or more, from the perspective of saving petroleum resources and reducing carbon dioxide emissions, an adhesive tape with a lower environmental burden can be made. The more preferred lower limit of the content of the above-mentioned biogenic carbon is 20% by weight or more, the further preferred lower limit is 40% by weight, the further preferred lower limit is 50% by weight, and the further preferred lower limit is 60% by weight. The upper limit of the content of the above-mentioned biogenic carbon is not particularly limited, and can be 100% by weight.
[0104] Among them, the biogenic carbon content of the foam substrate is more preferably 50% by weight or more, and the biogenic carbon content of the block copolymer is preferably 40% by weight or more, and more preferably 50% by weight or more.
[0105] The manufacturing method of the adhesive tape of the present invention is not particularly limited, and for example, the following method can be cited. First, an adhesive solution is applied to a release film, dried to form an adhesive layer, and a second adhesive layer is formed in the same manner. Next, an unfoamed substrate is manufactured by the above method, and the above resin layer is laminated on the above unfoamed substrate to form a laminate. Thereafter, the obtained adhesive layer is attached to both sides of the obtained laminate, and the unfoamed substrate is foamed by heating to manufacture the adhesive tape.
[0106] The shape of the pressure-sensitive adhesive tape of the present invention is not particularly limited, and examples thereof include rectangular, frame-shaped, circular, elliptical, and ring-shaped shapes.
[0107] The adhesive tape of the present invention can exhibit excellent flexibility and impact resistance by using the above-mentioned block copolymer as a foam substrate. On the other hand, the present inventors conducted research and found that: when the foam substrate contains a copolymer comprising the above-mentioned structure derived from a vinyl aromatic compound monomer and the above-mentioned structure derived from a (meth) acrylic acid-based monomer, even a random copolymer can exhibit excellent flexibility, impact resistance and heat resistance. This is believed to be because: at the extremely small level of the nanometer or molecular level, the same interaction as the above-mentioned phase separation structure is at work. It should be noted that the structure derived from the (meth) acrylic acid-based monomer in this specification refers to the structure shown in the following general formula (5) and (6).
[0108] [Chemical formula 3]
[0109]
[0110] Here, R 3 Represents a side chain. As a side chain R 3 , methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, 2-ethylhexyl, nonyl, decyl, dodecyl, lauryl, isostearyl and the like can be mentioned.
[0111] An adhesive tape has such a foam substrate and at least one adhesive layer, the foam substrate contains a copolymer, the copolymer has a structure derived from a vinyl aromatic compound monomer and a structure derived from a (meth)acrylic monomer, and the adhesive tape contains biogenic carbon. The adhesive tape (hereinafter also referred to as an adhesive tape containing a copolymer) is also one of the present invention.
[0112] The copolymer is not particularly limited and may be a random copolymer or a graft polymer.
[0113] As the vinyl aromatic compound monomer and the (meth)acrylic monomer, the same monomers as those used in the block copolymer can be used.
[0114] The above-mentioned copolymer preferably contains 1% by weight or more of the above-mentioned structure derived from the vinyl aromatic compound monomer, more preferably 2% by weight or more, further preferably 5% by weight or more, preferably 30% by weight or less, more preferably 19% by weight or less, further preferably 15% by weight or less, and further preferably 10% by weight or less.
[0115] The copolymer preferably contains 70% by weight or more, more preferably 81% by weight or more, and preferably 99% by weight or less, more preferably 98% by weight or less.
[0116] The above-mentioned copolymer preferably has a structure derived from a monomer having a crosslinkable functional group.
[0117] If the above-mentioned copolymer has a crosslinkable functional group, the rubber elasticity of the copolymer is improved by crosslinking, interaction between functional groups, etc., so the flexibility and impact resistance can be further improved. The above-mentioned crosslinkable functional group may be crosslinked or not crosslinked, and even if it is a structure that is not crosslinked, the cohesion is improved, the flexibility and impact resistance are improved by the interaction between functional groups, but it is more preferably crosslinked. It should be noted that in this specification, the structure from the monomer having a crosslinkable functional group refers to the structure shown in the following general formula (3) and (4).
[0118] [Chemical formula 4]
[0119]
[0120] Here, R 2 represents a substituent containing at least one functional group. Examples of the functional group include a carboxyl group, a hydroxyl group, an epoxy group, a double bond, a triple bond, an amino group, an amide group, and a nitrile group. 2 An alkyl group, an ether group, a carbonyl group, an ester group, a carbonate group, an amide group, a carbamate group or the like may be contained as its constituent elements.
[0121] The above-mentioned monomer with crosslinking functional group is not particularly limited, for example, monomers containing carboxyl groups, monomers containing hydroxyl groups, monomers containing epoxy groups, monomers containing double bonds, monomers containing triple bonds, monomers containing amino groups, monomers containing amide groups, monomers containing nitrile groups, etc. can be listed. Among them, from the perspective of further improving flexibility and impact resistance, it is preferably selected from at least one of the groups consisting of monomers containing hydroxyl groups, monomers containing carboxyl groups, monomers containing epoxy groups, monomers containing amide groups, monomers containing double bonds and monomers containing triple bonds. As monomers containing hydroxyl groups, 4-hydroxybutyl (methyl) acrylate, 2-hydroxyethyl (methyl) acrylate, etc. can be listed. As the above-mentioned monomers containing carboxyl groups, (methyl) acrylic acid, etc. can be listed. As monomers containing epoxy groups, (methyl) acrylic acid glycidyl ester, etc. can be listed. As monomers containing amide groups, (methyl) acrylamide, etc. can be listed. As monomers containing double bonds, allyl (methyl) acrylate, hexanediol di(methyl) acrylate, etc. can be listed. Examples of the triple bond-containing monomer include propargyl (meth)acrylate, etc. Among these, from the viewpoint of providing the pressure-sensitive adhesive tape with further excellent flexibility and impact resistance, a carboxyl group-containing monomer is preferred, a (meth)acrylic acid monomer is more preferred, and acrylic acid is further preferred.
[0122] The copolymer preferably contains 0.1% by weight or more and 30% by weight or less of the structure derived from the monomer having a crosslinkable functional group.
[0123] By making the content of the structure derived from the monomer having a crosslinkable functional group in the copolymer within the above range, the flexibility and impact resistance can be further improved. The more preferred lower limit of the content of the structure derived from the monomer having a crosslinkable functional group is 0.5% by weight, the more preferred lower limit is 1% by weight, the more preferred upper limit is 20% by weight, and the more preferred upper limit is 10% by weight.
[0124] As a method for producing the above-mentioned copolymer, for example, a solution of a vinyl aromatic compound monomer, a (meth) acrylic acid monomer, and a monomer having a crosslinking functional group as required and other monomers is mixed, and free radical reaction is carried out in the presence of a polymerization initiator. As a method for making the free radical reaction, a conventionally known method is used, for example, solution polymerization (boiling point polymerization or constant temperature polymerization), emulsion polymerization, suspension polymerization, bulk polymerization, etc. can be cited.
[0125] The copolymer-containing pressure-sensitive adhesive tape of the present invention preferably has a bio-derived carbon content of 10% by weight. A bio-derived carbon content of 10% by weight or more is a criterion for a "bio-based product."
[0126] By making the content of biogenic carbon in the adhesive tape containing the copolymer of the present invention 10% by weight or more, from the perspective of saving petroleum resources and reducing the emission of carbon dioxide, an adhesive tape with a lower environmental burden can be made. The more preferred lower limit of the content of the above-mentioned biogenic carbon is 20% by weight or more, the further preferred lower limit is 40% by weight, the further preferred lower limit is 50% by weight, and the further preferred lower limit is 60% by weight. The upper limit of the content of the above-mentioned biogenic carbon is not particularly limited and can be 100% by weight.
[0127] Among them, the biogenic carbon content of the foam substrate is more preferably 50% by weight or more, and the biogenic carbon content of the copolymer is even more preferably 50% by weight or more.
[0128] In the adhesive tape containing a copolymer of the present invention, the material of the foam substrate other than the copolymer, as well as its content, apparent density, gel fraction, average cell diameter, thickness, and manufacturing method can be the same as those of the foam substrate of the adhesive tape using the block copolymer.
[0129] In the copolymer-containing pressure-sensitive adhesive tape of the present invention, the pressure-sensitive adhesive layer may be the same pressure-sensitive adhesive layer as that of the pressure-sensitive adhesive tape using the block copolymer.
[0130] The copolymer-containing pressure-sensitive adhesive tape of the present invention may use the same components as those of the pressure-sensitive adhesive tape using the block copolymer described above, except for the foam substrate and the pressure-sensitive adhesive layer.
[0131] Effects of the Invention
[0132] According to the present invention, a pressure-sensitive adhesive tape having excellent flexibility and impact resistance and low environmental load can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0133] Figure 1 (a) is a front view showing the state of the holding force test of the adhesive tape.
[0134] Figure 1 (b) is a side view showing the state of the holding force test of the adhesive tape. DETAILED DESCRIPTION
[0135] The embodiments of the present invention are described in further detail below with reference to examples, but the present invention is not limited to these examples.
[0136] (Example 1)
[0137] (1) Production of unfoamed substrate
[0138] 0.902 g of 1,6-hexanedithiol, 1.83 g of carbon disulfide and 11 mL of dimethylformamide were placed in a two-necked flask and stirred at 25°C. 2.49 g of triethylamine was dripped into the mixture over 15 minutes, and the mixture was stirred at 25°C for 3 hours. Next, 2.75 g of methyl α-bromophenylacetate was dripped into the mixture over 15 minutes, and the mixture was stirred at 25°C for 4 hours. After that, 100 mL of an extraction solvent (n-hexane: ethyl acetate = 50:50) and 50 mL of water were added to the reaction solution, and the mixture was separated and extracted. The organic layers obtained by the first and second extractions were mixed, and washed with 50 mL of 1M hydrochloric acid, 50 mL of water, and 50 mL of saturated brine in sequence. Sodium sulfate was added to the washed organic layer for drying, and the sodium sulfate was filtered off. The filtrate was concentrated using an evaporator to remove the organic solvent. The obtained concentrate was purified by silica gel column chromatography to obtain a RAFT agent.
[0139] 87 parts by weight of styrene (St), 12 parts by weight of acrylic acid (AAc), 1 part by weight of hydroxyethyl acrylate (HEA), 1.9 parts by weight of a RAFT agent, and 0.2 parts by weight of 2,2'-azobis(2-methylbutyronitrile) (ABN-E) were placed in a two-necked flask, and the temperature was raised to 85° C. while replacing the inside of the flask with nitrogen. Thereafter, the polymerization reaction (first stage reaction) was carried out by stirring at 85° C. for 6 hours.
[0140] After the reaction was completed, 4000 parts by weight of n-hexane was added to the flask, stirred to precipitate the reactants, and then unreacted monomers (St, AA, HEA) and RAFT agent were filtered out. The reactants were dried under reduced pressure at 70°C to obtain a copolymer (hard block).
[0141] A mixture containing 50 parts by weight of butyl acrylate (BA, non-biological source), 50 parts by weight of n-heptyl acrylate (nHPA, biological source), 0.058 parts by weight of ABN-E, and 50 parts by weight of ethyl acetate, and the copolymer obtained above (hard block) were put into a two-necked flask, and the temperature was raised to 85°C while replacing the flask with nitrogen. After that, the polymerization reaction (second stage reaction) was carried out at 85°C for 6 hours with stirring to obtain a reaction solution containing a block copolymer formed by a hard block and a block (soft block) from a (meth) acrylic acid monomer. It should be noted that the amount of the mixture (block and hard block from a (meth) acrylic acid monomer) is set to an amount such that the content of the hard block in the obtained block copolymer is 17% by weight.
[0142] A portion of the reaction solution was extracted, 4000 parts by weight of n-hexane was added thereto, and after stirring to precipitate the reactant, the unreacted monomers (BA, nHPA) and the solvent were filtered, and the reactant was dried under reduced pressure at 70°C to remove the block copolymer from the reaction solution. The weight average molecular weight of the obtained block copolymer measured by the GPC method was 250,000. The above weight average molecular weight was measured as follows: using the "2690Separations Module" manufactured by Waters as a measuring machine, using the "GPC KF-806L" manufactured by Showa Denko as a chromatographic column, using ethyl acetate as a solvent, and measuring under the conditions of a sample flow rate of 1 mL / min and a chromatographic column temperature of 40°C.
[0143] The obtained block copolymer was dissolved in ethyl acetate in such a manner that the solid content was 35%. 0.30 parts by weight of Expancel 461-40 (manufactured by Fillite Co., Ltd. of Japan, recorded as DU40 in the table) as a foaming agent and 0.2 parts by weight of TETRAD C (manufactured by Mitsubishi Gas Chemical Co., Ltd.) as a crosslinking agent were added to 100 parts by weight of the block copolymer and stirred further to obtain a substrate solution. The obtained substrate solution was applied to the release-treated surface of a 50 μm polyethylene terephthalate (PET) film with a release treatment on one side, and dried at 90° C. for 7 minutes to obtain an unfoamed substrate. The thickness of the unfoamed substrate was adjusted to 100 μm when the unfoamed substrate was heated at 130° C. for 1 minute.
[0144] (2) Preparation of adhesive solution
[0145] 52 parts by weight of ethyl acetate were added to a reactor equipped with a thermometer, a stirrer, and a cooling tube. After nitrogen substitution, the reactor was heated to start reflux. After ethyl acetate was boiled for 30 minutes, 0.08 parts by weight of azobisisobutyronitrile was added as a polymerization initiator. A monomer mixture containing 70 parts by weight of butyl acrylate, 27 parts by weight of 2-ethylhexyl acrylate, 3 parts by weight of acrylic acid, and 0.2 parts by weight of 2-hydroxyethyl acrylate was dripped therein at a uniform speed and slowly for 1 hour and 30 minutes to react. 0.1 parts by weight of azobisisobutyronitrile was added 30 minutes after the dripping was completed, and the polymerization reaction was further performed for 5 hours. Ethyl acetate was added to the reactor and cooled while diluting, thereby obtaining a solution of an acrylic random copolymer with a solid content of 40% by weight.
[0146] The weight average molecular weight of the obtained acrylic random copolymer measured by the GPC method was 710,000. The ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) was 5.5. The weight average molecular weight and the number average molecular weight were measured as follows: using the "2690 Separations Module" manufactured by Waters as a measuring machine, the "GPC KF-806L" manufactured by Showa Denko as a chromatographic column, and ethyl acetate as a solvent, and measuring under the conditions of a sample flow rate of 1 mL / min and a chromatographic column temperature of 40°C.
[0147] 15 parts by weight of polymerized rosin ester with a softening point of 150° C., 10 parts by weight of terpene phenol with a softening point of 145° C., and 10 parts by weight of rosin ester with a softening point of 70° C. were added to 100 parts by weight of the solid content of the obtained acrylic random copolymer. Furthermore, 30 parts by weight of ethyl acetate (manufactured by Fuji Chemicals Co., Ltd.) and 3.0 parts by weight of an isocyanate crosslinking agent (Coronate L45 manufactured by Tosoh Corporation) were added, and stirred to obtain an adhesive solution.
[0148] (3) Manufacturing of adhesive tape
[0149] On the demoulding treatment surface of a 50 μm polyethylene terephthalate (PET) film with demoulding treatment applied on one side, the obtained adhesive solution is applied with a scraper in a manner that the thickness of the dry coating becomes 50 μm, and the coating solution is dried by heating at 110°C for 5 minutes to obtain an adhesive layer. Next, another adhesive layer is manufactured using the same steps to obtain two adhesive layers. After this, the demoulding film is peeled off from the unfoamed substrate obtained above, and the two obtained adhesive layers are respectively attached to the two sides of the unfoamed substrate and left to stand for 48 hours in an environment of 40°C. After 48 hours, it is taken out from the 40°C environment, and the substrate is foamed by heating at 130°C for 1 minute to obtain an adhesive tape.
[0150] (4) Determination of band density
[0151] The density of the obtained pressure-sensitive adhesive tape was measured using an electronic densitometer (ED120T, manufactured by MIRAGE).
[0152] (5) Determination of apparent density of foam substrate
[0153] The density of the obtained foam substrate was measured in accordance with JIS K 7222 using an electronic densitometer (ED120T manufactured by MIRAGE).
[0154] (6) Measurement of gel fraction of foam substrate
[0155] Only 0.1 g of the foam substrate was taken out from the obtained adhesive tape, immersed in 50 ml of ethyl acetate, and shaken for 24 hours with a shaker at a temperature of 23 degrees and 120 rpm. After shaking, a metal mesh (mesh #200 mesh) was used to separate the ethyl acetate and the foam substrate that absorbed the ethyl acetate and swelled. The separated foam substrate was dried at 110°C for 1 hour. The weight of the foam substrate including the dried metal mesh was measured, and the gel fraction of the foam substrate was calculated by the following formula.
[0156] Gel fraction (weight %) = 100 × (W1-W2) / W0
[0157] (W0: initial weight of foam substrate, W1: weight of foam substrate including metal mesh after drying, W2: initial weight of metal mesh)
[0158] (7) Determination of the biogenic carbon content of adhesive tapes and substrates
[0159] The obtained pressure-sensitive adhesive tape and foam substrate were measured for carbon radioisotope ( 14 C), thereby determining the biogenic carbon content of the adhesive tape and the substrate.
[0160] (Examples 2 to 15, Comparative Examples 1 to 3)
[0161] The adhesive tape was obtained in the same manner as in Example 1 except that the composition, apparent density, thickness and amount of foaming agent of the foam substrate were set as shown in Table 1. As for Comparative Examples 1 and 3, since they did not contain a foaming agent, they were still in an unfoamed state after being heated at 130°C for 1 minute. As for the obtained adhesive tape and foam substrate (Comparative Examples 1 and 3 were unfoamed substrates), various measurements were performed in the same manner as in Example 1. In Comparative Example 2, SIS (styrene-isoprene block copolymer, manufactured by ZEON Corporation of Japan, Quintac3421) was used as a block copolymer constituting the foam substrate. It should be noted that the raw materials in the table are as follows.
[0162] nOA: n-octyl acrylate (biosource)
[0163] 1-MHA: 1-Methylheptyl acrylate (biosource)
[0164] LA: Lauryl acrylate (bio-sourced)
[0165] LMA: Lauryl Methacrylate (bio-sourced)
[0166] IBOA: Isobornyl acrylate (biologically derived)
[0167] Isoprene: Non-(meth)acrylic monomer (non-biological origin)
[0168] (Examples 16, 17)
[0169] (1) Production of unfoamed substrate
[0170] Except having set the composition as shown in Table 1, it carried out similarly to Example 1, and obtained the unfoamed body base material.
[0171] (2) Preparation of adhesive solution
[0172] In the reaction vessel, ethyl acetate as a polymerization solvent was added, and after bubbling with nitrogen, the reaction vessel was heated while nitrogen was flowing in to start reflux. Next, a polymerization initiator solution obtained by diluting 10 times of 0.1 weight part of azobisisobutyronitrile with ethyl acetate as a polymerization initiator was put into the reaction vessel, and 96.9 weight parts of n-heptyl acrylate (biological source), 2.9 weight parts of acrylic acid and 0.1 weight part of 2-hydroxyethyl acrylate were added dropwise over 2 hours. After the dropwise addition was completed, a polymerization initiator solution obtained by diluting 10 times of 0.1 weight part of azobisisobutyronitrile with ethyl acetate as a polymerization initiator was put into the reaction vessel again, and a polymerization reaction was carried out for 4 hours to obtain a solution containing an acrylic random copolymer.
[0173] The weight average molecular weight of the obtained acrylic random copolymer measured by the GPC method was 1 million. The ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) was 5.5. The weight average molecular weight and the number average molecular weight were measured as follows: using the "2690 Separations Module" manufactured by Waters as a measuring machine, the "GPC KF-806L" manufactured by Showa Denko as a chromatographic column, and ethyl acetate as a solvent, and measuring under the conditions of a sample flow rate of 1 mL / min and a chromatographic column temperature of 40°C.
[0174] 15 parts by weight of polymerized rosin ester with a softening point of 150° C., 10 parts by weight of terpene phenol with a softening point of 145° C., and 10 parts by weight of rosin ester with a softening point of 100° C. were added to 100 parts by weight of the solid content of the obtained acrylic random copolymer. Furthermore, 30 parts by weight of ethyl acetate (manufactured by Fuji Chemicals Co., Ltd.) and 0.2 parts by weight of an isocyanate crosslinking agent (Coronate L45 manufactured by Tosoh Corporation) were added, and stirred to obtain an adhesive solution.
[0175] (3) Manufacturing of adhesive tape
[0176] A pressure-sensitive adhesive tape was obtained in the same manner as in Example 1 except that the obtained unfoamed substrate and pressure-sensitive adhesive solution were used. The same various measurements as in Example 1 were performed on the obtained pressure-sensitive adhesive tape.
[0177] (Example 18)
[0178] (1) Production of unfoamed substrate
[0179] 52 parts by weight of ethyl acetate were added to a reactor equipped with a thermometer, a stirrer, and a cooling tube. After nitrogen substitution, the reactor was heated to start reflux. After ethyl acetate was boiled for 30 minutes, 0.08 parts by weight of azobisisobutyronitrile was added as a polymerization initiator. A monomer mixture containing 90 parts by weight of n-heptyl acrylate, 9 parts by weight of styrene (St, non-biological source), and 1 part by weight of acrylic acid (AAc, non-biological source) was uniformly and slowly added thereto for 1 hour and 30 minutes to react. 30 minutes after the dripping was completed, 0.1 parts by weight of azobisisobutyronitrile was added, and the polymerization reaction was further performed for 5 hours. Ethyl acetate was added to the reactor and cooled while diluting to obtain a solution of a random copolymer with a solid content of 40% by weight.
[0180] The weight average molecular weight of the obtained random copolymer measured by the GPC method was 350,000. The weight average molecular weight was measured as follows: using "2690 Separations Module" manufactured by Waters as a measuring machine, using "GPC KF-806L" manufactured by Showa Denko as a chromatographic column, using ethyl acetate as a solvent, and measuring under the conditions of a sample flow rate of 1 mL / min and a chromatographic column temperature of 40°C.
[0181] The obtained random copolymer was dissolved in ethyl acetate so that the solid content was 35%, and 0.30 parts by weight of Expancel 461-40 as a foaming agent and 0.2 parts by weight of TETRAD C as a crosslinking agent were added to 100 parts by weight of the random copolymer, and the mixture was further stirred sufficiently to obtain a base material solution. The obtained base material solution was applied to a release-treated surface of a 50 μm polyethylene terephthalate (PET) film with a release treatment on one side, and dried at 90° C. for 7 minutes to obtain an unfoamed base material containing a graft copolymer. The thickness of the unfoamed base material was adjusted to 100 μm when the unfoamed base material was heated at 130° C. for 1 minute.
[0182] (2) Manufacturing of adhesive tape
[0183] A pressure-sensitive adhesive tape was obtained in the same manner as in Example 1 except that the obtained non-foamed substrate made of the random copolymer was used. The same various measurements as in Example 1 were performed on the obtained pressure-sensitive adhesive tape.
[0184] (Examples 19 to 21, Comparative Example 4)
[0185] A pressure-sensitive adhesive tape was obtained in the same manner as in Example 18 except that the composition of the foam substrate was set as shown in Table 2. The same various measurements as in Example 1 were performed on the pressure-sensitive adhesive tape obtained.
[0186] <Evaluation>
[0187] The pressure-sensitive adhesive tapes obtained in Examples and Comparative Examples were evaluated as follows.
[0188] (Evaluation of impact resistance)
[0189] The obtained adhesive tape was punched out into a square shape with a size of 45mm×60mm and a width of 1mm. One side of the punched adhesive tape was attached to the center of a square-shaped stainless steel plate of 80mm×115mm and a thickness of 2mm with a hole of 40mm×40mm in the center. Next, a 50mm×70mm, 4mm thick tempered glass plate was attached to the other side of the adhesive tape, and a 5kg weight was used to press it for 10 seconds, and it was left to stand at 23°C for 24 hours to obtain a test laminate. The obtained laminate was fixed to a stainless steel frame (inner diameter 60mm×90mm) in such a way that the tempered glass plate became as follows. Thereafter, a 150g iron ball was dropped into the center of the tempered glass plate. The height from which the iron ball was dropped was increased, and the height of the iron ball was measured when the tempered glass plate was peeled off from the stainless steel plate. Impact resistance was evaluated by indicating that the height of the iron ball when the tempered glass plate was peeled off from the stainless steel plate was 50 cm or more, 40 cm or more and less than 50 cm, and less than 40 cm.
[0190] (Evaluation of holding power)
[0191] Figure 1 In the figure, a schematic diagram illustrating the holding force test of the adhesive tape is shown. First, one side (surface) of a test piece 1 of the adhesive tape having a size of 25 mm × 25 mm is bonded to a SUS plate 2, and a 2 kg rubber roller is used to reciprocate it once at a speed of 300 mm / min from the other side (back side) of the test piece 1. Next, an aluminum plate 3 is bonded to the back side of the test piece 1, and after being pressed for 10 seconds with a 0.5 kg weight from the aluminum plate 3 side, it is placed in an environment of 23°C and a relative humidity of 50% for 24 hours to prepare a holding force test sample. Such a holding force test sample is installed at 100°C with a 0.5 kg or 1.0 kg weight 4 at one end of the aluminum plate 3, relative to the test piece 1 and the aluminum plate 3, and the displacement length of the weight is measured after 1 hour. In addition, a 1.0 kg weight 4 is installed and the displacement length is also measured after 2 hours. The obtained measurement results were evaluated for holding power by marking “◎” for a displacement length of 0 (no displacement), “○” for a displacement length of more than 0 and less than 1 mm, and “×” for a displacement length of 1 mm or more or when the adhesive tape peeled and fell off.
[0192] (Evaluation of compression strength)
[0193] The 25% compression strength of the obtained double-sided adhesive tape was calculated in accordance with JIS K-6767, and the obtained value was evaluated as "◎" when it was 50 kPa or less, "○" when it was more than 50 kPa and less than 80 kPa, and "×" when it was more than 80 kPa.
[0194]
[0195]
[0196] Industrial Applicability
[0197] According to the present invention, a pressure-sensitive adhesive tape having excellent flexibility and impact resistance and low environmental load can be provided.
[0198] Description of Reference Numerals
[0199] 1. Adhesive tape test piece size 25mm x 25mm
[0200] 2 SUS board
[0201] 3 Aluminum Plate
[0202] 4 Heavy objects (0.5kg or 1.0kg)
Claims
1. An adhesive tape comprising a foam substrate and at least one adhesive layer, wherein: The foam substrate contains a block copolymer having a block derived from a (meth)acrylic monomer, and the adhesive tape contains biogenic carbon. The block copolymer has at least one hard block, The hard block has a structure derived from a vinyl aromatic compound monomer.
2. The adhesive tape according to claim 1, wherein The block copolymer contains 1 wt % or more and 40 wt % or less of the hard block.
3. The adhesive tape according to claim 1 or 2, wherein The content of the structure derived from the vinyl aromatic compound monomer in the block copolymer is 1% by weight or more and 30% by weight or less.
4. The adhesive tape according to claim 1 or 2, wherein The hard block has a structure derived from a monomer having a crosslinkable functional group.
5. The adhesive tape according to claim 4, wherein The hard block contains 0.1% by weight or more and 30% by weight or less of the structure derived from the monomer having a crosslinkable functional group.
6. The adhesive tape according to claim 1 or 2, wherein The foam substrate contains biogenic carbon.
7. The adhesive tape according to claim 1 or 2, wherein The (meth)acrylic acid-based monomer contains a (meth)acrylic acid-based monomer containing biogenic carbon.
8. The adhesive tape according to claim 7, wherein The (meth)acrylic acid monomer containing biogenic carbon has an alkyl group having 7 to 12 carbon atoms.
9. The adhesive tape according to claim 7, wherein The (meth)acrylic acid-based monomer containing biogenic carbon is a (meth)acrylic acid-based monomer having a homopolymer having a glass transition temperature Tg of -40°C or less.
10. The adhesive tape according to claim 7, wherein The (meth)acrylic monomer containing biogenic carbon is n-heptyl acrylate or n-octyl acrylate.
11. The adhesive tape according to claim 1 or 2, wherein The adhesive tape has a biogenic carbon content of 50% by weight or more.
12. The adhesive tape according to claim 1 or 2, wherein The content of biogenic carbon in the foam substrate is 50% by weight or more.
13. The adhesive tape according to claim 1 or 2, wherein The block copolymer has a biogenic carbon content of 50% by weight or more.
14. The adhesive tape according to claim 1 or 2, wherein The apparent density of the foam substrate is 0.3 g / cm 3 Above 0.95g / cm 3 the following.
15. The adhesive tape according to claim 1 or 2, wherein The gel fraction of the foam substrate is 90% or less.
16. The adhesive tape according to claim 1 or 2, wherein The average cell diameter of cells in the foam substrate is 80 μm or less.
17. The adhesive tape according to claim 1 or 2, wherein: The foam substrate has a thickness of 40 μm or more and 2900 μm or less.
18. An adhesive tape comprising a foam substrate and at least one adhesive layer, wherein: The foam substrate contains a copolymer, The foam substrate has a gel fraction of 10% or more and 41% or less, The copolymer has a structure derived from a vinyl aromatic compound monomer and a structure derived from a (meth)acrylic monomer, The content of the structure derived from the (meth)acrylic acid-based monomer in the copolymer is 70% by weight or more and 98% by weight or less, The (meth)acrylic acid monomer contains a (meth)acrylic acid monomer containing biogenic carbon, The (meth)acrylic acid monomer containing biogenic carbon has an alkyl group having 7 to 12 carbon atoms, The adhesive tape contains biogenic carbon.
19. The adhesive tape according to claim 18, wherein The copolymer has a structure derived from a monomer having a crosslinkable functional group.
20. The adhesive tape according to claim 19, wherein The copolymer contains 0.1% by weight or more and 30% by weight or less of the structure derived from the monomer having a crosslinkable functional group.
21. The adhesive tape according to claim 18 or 19, wherein The foam substrate contains biogenic carbon.
22. The adhesive tape according to claim 18 or 19, wherein The apparent density of the foam substrate is 0.3 g / cm 3 Above 0.95g / cm 3 the following.
23. The adhesive tape according to claim 18 or 19, wherein The average cell diameter of cells in the foam substrate is 80 μm or less.
24. The adhesive tape according to claim 18 or 19, wherein The foam substrate has a thickness of 40 μm or more and 2900 μm or less.
25. The adhesive tape according to claim 18 or 19, wherein The (meth)acrylic acid-based monomer containing biogenic carbon is a (meth)acrylic acid-based monomer having a homopolymer having a glass transition temperature Tg of -40°C or less.
26. The adhesive tape according to claim 18 or 19, wherein The (meth)acrylic monomer containing biogenic carbon is n-heptyl acrylate or n-octyl acrylate.
27. The adhesive tape according to claim 18 or 19, wherein The adhesive tape has a biogenic carbon content of 50% by weight or more.
28. The adhesive tape according to claim 18 or 19, wherein The content of biogenic carbon in the foam substrate is 50% by weight or more.
29. The adhesive tape according to claim 18 or 19, wherein The copolymer has a biogenic carbon content of 50% by weight or more.
Citation Information
Patent Citations
Impact-absorbing tape
JP2009242541A
Pressure-sensitive adhesive sheet for front plate of display device
JP2009258274A
Tape base and adhesive tape
CN101454394A
Shock-absorbing sheet
WO2019066020A1